REFORMASI HAK-HAK PEREMPUAN ARAB SAUDI MELALUI SAUDI VISION 2030 TAHUN 2017-2019 - Mufiedah, Analieza Ilmiatun; Harini, Setyasih; Haqqi, Halifa (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
This research describes and analyse about the reformation of women’s rights in Saudi Arabia along with the announcement of Saudi Vision 2030. Saudi Vision 2030 made because the Kingdom of Saudi Arabia wants to end its economic liability on oil and gas reserve. This research uses liberal feminism and constructivism theory. The purpose of this research is to establish about how Saudi Vision 2030 made few changes on the reformation of Saudi women’s rights. This research uses qualitative method with secondary data collection and uses descriptive method. From the data collected, the writer analyses that Saudi Vision 2030 has made some mignificant changes to Saudi women’s rights with some new policies made through 2017-2019 period of time which more gender friendly to achieve the goals of Saudi Vision 2030 so that Saudi Arabia no longer depending its economic sector on oil and gas reserves. Keywords: Saudi Vision 2030, women’s rights reformations, Saudi Arabia